Heterogeneity of Alkane Chain Length in Freshwater and Marine Cyanobacteria - Shakeel, Tabinda; Fatma, Zia; Fatma, Tasneem; Yazdani, Syed Shams (Frontiers in Bioengineering and Biotechnology, 2015)
The potential utilization of cyanobacteria for the biological production of alkanes represents an exceptional system for the next generation of biofuels. Here, we analyzed a diverse group of freshwater and marine cyanobacterial isolates from Indian culture collections for their ability to produce both alkanes and alkenes. Among the 50 cyanobacterial isolates screened, 32 isolates; 14 fresh water and 18 marine isolates; produced predominantly alkanes. The GC-MS/MS profiles revealed a higher percentage of pentadecane and heptadecane production for marine and fresh water strains, respectively. Oscillatoria species were found to be the highest producers of alkanes. Among the fresh water isolates, Oscillatoria CCC305 produced the maximum alkane level with 0.43 μg /mg dry cell weight, while Oscillatoria formosa BDU30603 was the highest producer among the marine isolates with 0.13 μg /mg dry cell weight. Culturing these strains under different media compositions showed that the alkane chain length was not influenced by the growth medium but was rather an inherent property of the strains. Analysis of the cellular fatty acid content indicated the presence of predominantly C16 chain length fatty acids in marine strains, while the proportion of C18 chain length fatty acids increased in the majority of freshwater strains. These results correlated with alkane chain length specificity of marine and fresh water isolates indicating that alkane chain lengths may be primarily determined by the fatty acid synthesis pathway. Moreover, the phylogenetic analysis showed clustering of pentadecane-producing marine strains that was distinct from heptadecane-producing freshwater strains strongly suggesting a close association between alkane chain length and the cyanobacteria habitat.